2009
DOI: 10.1523/jneurosci.5741-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Amyloid Deposition in Mice Overexpressing RTN3 Is Adversely Affected by Preformed Dystrophic Neurites

Abstract: Reticulon 3 (RTN3) was initially identified as a negative modulator of BACE1, an enzyme that cleaves amyloid precursor protein (APP) to release ␤-amyloid peptide. Interestingly, RTN3 can also form aggregates after accumulation, and increased RTN3 aggregation correlates with the formation of RTN3 immunoreactive dystrophic neurites (RIDNs) in brains of Alzheimer's cases. Transgenic mice expressing RTN3 alone develop RIDNs in their hippocampus but not in their cortex. To determine the in vivo effects of RTN3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 60 publications
2
60
0
Order By: Relevance
“…RTNLB1 and RTNLB2 are known to interact through their reticulon domains (Hwang and Gelvin, 2004;Sparkes et al, 2010); thus, they may function as a heterodimer or as part of a larger protein complex to regulate FLS2 secretion. Furthermore, considering the role of the human RTNs in intracellular protein trafficking (Wakana et al, 2005;He et al, 2006;Liu et al, 2008;Chang et al, 2009;Shi et al, 2009;Yang et al, 2009), our findings indicate functional conservation between RTNs and plant RTNLBs.…”
Section: Rtnlb1 and Rtnlb2 Are Components Of The Fls2 Secretory Pathwaymentioning
confidence: 64%
“…RTNLB1 and RTNLB2 are known to interact through their reticulon domains (Hwang and Gelvin, 2004;Sparkes et al, 2010); thus, they may function as a heterodimer or as part of a larger protein complex to regulate FLS2 secretion. Furthermore, considering the role of the human RTNs in intracellular protein trafficking (Wakana et al, 2005;He et al, 2006;Liu et al, 2008;Chang et al, 2009;Shi et al, 2009;Yang et al, 2009), our findings indicate functional conservation between RTNs and plant RTNLBs.…”
Section: Rtnlb1 and Rtnlb2 Are Components Of The Fls2 Secretory Pathwaymentioning
confidence: 64%
“…Interestingly, we found that RTN3 participates in the induction of neuronal pathology in diabetic rat brains because diabetes reduced the levels of monomeric RTN3 and increased the formation of oligomeric RTN3 (Figs. 3 and 6), which are associated with neurodegeneration and neurological dysfunction (29,30). In fact, mono-RTN3 endogenously inhibits BACE1 enzyme activity via complex formation between RTN3 and BACE1 (30,36).…”
Section: Discussionmentioning
confidence: 99%
“…3 and 6), which are associated with neurodegeneration and neurological dysfunction (29,30). In fact, mono-RTN3 endogenously inhibits BACE1 enzyme activity via complex formation between RTN3 and BACE1 (30,36). Therefore, mono-RTN3 reduction will theoretically cause an increase in BACE1 activity and A␤ generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 -Correlation between some reticulon cellular functions and their potential pathological implication. association of RTN3 with BACE1 alters its trafficking itinerary to the cell surface [27].…”
Section: Reticulons In Membrane Traffickingmentioning
confidence: 99%